Kontrola jakości w firmie audytorskiej - Szafraniec, Jadwiga (Quality Control in Audit Companies, 2007)
The aim of this article is to formulate the necessity of well organized system of internal control in order to reach the suitable level of audit services quality. What is important, audit services quality should be crucial element of any audit company. Therefore, clear and coherent patterns of auditors' evaluation procedures should be made by the managers. Ethical issues, specified in the International Code of Ethics (IFAC) are also a significant element of audit services quality.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 152-157